Clinical characteristics in young-adult ALS – results from a Portuguese cohort study. Issue 7 (1st October 2020) - Oliveira Santos, Miguel; Gromicho, Marta; Pinto, Susana; De carvalho, Mamede
Abstract: Objective: Studies concerning young-adult amyotrophic lateral sclerosis (yALS) are uncommon, due to the rarity of this condition. We aimed to investigate this subject. Methods: A retrospective-prospective study was conducted in our ALS center, including 1278 ALS patients followed longitudinally. Patients were divided in two groups - yALS (onset ≤40 years) and adult-onset ALS (aALS, onset >40 years). We analyzed phenotype, survival and genetics. Results: Sixty-three out of 1278 (4.9%) patients were included in yALS group, while the majority were categorized as aALS (1215, 95.1%). Juvenile ALS (onset < 25 years) represented 14.3% (9 patients) of yALS. In yALS group mean onset age was 32.5 ± 6.6 years (14–40) and 68.3% were men. Spinal-onset was significantly more frequent in yALS ( p  < 0.001), while bulbar-onset was more common in aALS ( p  = 0.002). Diagnostic delay was longer in yALS group ( p  = 0.02). yALS patients survived longer than aALS (88.2 ± 81.9 versus 41.1 ± 34, p  < 0.001), and functional decay was the only independent predictor found in the younger group ( p  = 0.007). No other significant differences were found, including familial history of ALS. Three yALS patients (4.8%) had C9orf72, SOD1 and FUS mutations identified by single-gene testing. A panel of 50 ALS-related genes investigated with next-generation sequencing in 9 yALS patients revealed no pathogenic mutation. Conclusions: yALS is a rare and specific ALS group. Disease progression is slower and survival longer in yALS, moreover and bulbar-onset phenotype is less common than in aALS. These observations are relevant to inform patients and for clinical trials design.